1991
DOI: 10.1093/ptj/71.2.90
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Goniometric Measurements and Visual Estimates of Knee Range of Motion Obtained in a Clinical Setting

Abstract: The purpose of this study was to examine the intratester and intertester reliability for goniometric measurements of knee flexion and extension passive range of motion (PROM). In addition, parallel-forms reliability for PROM measurements of the knee obtained by use of a goniometer and by visual estimation was examined. The intertester reliability for visual estimates of the PROM of the knee was also examined. Repeated measurements were obtained on 43 patients in a clinical setting. The intraclass correlation c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
182
1
18

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 298 publications
(226 citation statements)
references
References 5 publications
14
182
1
18
Order By: Relevance
“…Brosseauet al 15 found ICC of 0.99 for knee flexion and 0.97 for knee extension. The data by Watkins et al 16 corroborate the findings from this previous study, since very high reliability levels have been verified for the knee ROM measurements (ICC> 0.90). Rothstein et al 17 , when evaluated the intra examiner reliability of the knee and elbow movements also obtained very high ICC (> 0.91).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Brosseauet al 15 found ICC of 0.99 for knee flexion and 0.97 for knee extension. The data by Watkins et al 16 corroborate the findings from this previous study, since very high reliability levels have been verified for the knee ROM measurements (ICC> 0.90). Rothstein et al 17 , when evaluated the intra examiner reliability of the knee and elbow movements also obtained very high ICC (> 0.91).…”
Section: Discussionsupporting
confidence: 86%
“…The interexaminer measurements with small reliability were the elbow extension measurements, moderate for the knee extension measurements and the elbow flexion with goniometer, high for elbow flexion measurement with inclinometer and very high for all knee flexion measurements. Many authors report that the intraexaminerreliability presents higher values than interexaminer reliability 16,21 . The findings of the present study partially agree with the data from the literature, since even in the inter examiner evaluation of the present study it was possible to observe expressive results.…”
Section: Discussionmentioning
confidence: 99%
“…Correlation coefficients of intratester measurements of flexion and extension when using goniometers were reported to be 0.99 and 0.98, respectively. Similarly, intertester goniometric reliability of flexion and extension is on the order of 0.90 and 0.86 for flexion and extension, respectively [34]. Second, complete knee scores were unavailable for 34 of the 96 patients in the study and therefore were omitted from the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Bilateral elbow and knee extension values were measured using a goniometer to dichotomise joints as hypermobile or non-hypermobile (Norkin and White, 1995). Knee and elbow goniometric measurement have been shown to have good intra-rater reliability and moderate inter-rater reliability (Watkins et al, 1991;Chunang et al, 2007). Anthropometric measurements and playing position were also recorded.…”
Section: Methodsmentioning
confidence: 99%